PENYULUHAN MANAJEMEN BISNIS SYARIAH MASYARAKAT TAMAN NASIONAL GUNUNG HALIMUN SALAK PADA MASA PANDEMI COVID-19 DI KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Bayu Purnama Putra; Siti Evi Alfiah (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
During the Covid-19 pandemic, all people felt its influence. The people around the Mount Halimun Salak National Park (GHSNP) are no exception, which is included in the Pamijahan District, Bogor Regency. This has added to the burden on the community, which previously often faced problems with the degradation of natural resources and the environment, the low economic status of the community and the increasing population in the GHSNP area. In this regard, community service activities in the form of counseling on sharia business management are carried out in the TNGHS community which is included in the Pamijahan District area. This community service is to provide enlightenment regarding Islamic economics and business and especially sharia business management. In addition to providing moral reinforcement in the midst of the Covid-19 pandemic.